DICRITIC FOLIATION WITHOUT SINGULARITIES AFTER A BLOW-UP - Benazic Tomé, Renato Mario (2008)
In this paper we are going to study foliations defined by holomorphic vector fields with isolated singularity in the origin with dicritic type, which strict transformed doesn't present singularities and satisfies the t-condition. We will prove that this family is open and dense; also we will give local forms of every point of the divisor.